Real driving cycles and emissions for urban freight transport - Azevedo, Julie Anne Holanda; Cassiano, Demostenis Ramos; Bertoncini, Bruno Vieira (Frontiers in Big Data, 2024)
This paper aims to evaluate the driving style effects, through the construction of driving cycles, on the polluting gases, in the context of urban freight transportation. For this, the method used was the construction of cycles through the Vehicle Specific Power (VSP) parameter, which considers instantaneous vehicle and road parameters better to represent driving patterns and freight transportation's environmental impacts. The study was conducted in Fortaleza city, Ceará, Brazil, with a professional driver's group. The road types, land use and traffic light location were considered to analyze and discuss the results. The results show collector roads presented higher speeds than arterial roads, and the use of the land around the road also directly impacted vehicle driving patterns. Regarding CO2 emissions, higher concentrations measured were observed on the arterial roads.